2020
DOI: 10.1002/jbmr.4527
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Prevents Cartilage Degradation in Early-Stage Osteoarthritis Through Activation of miR-146a/NRF2/HO-1 Axis

Abstract: Reactive oxygen species (ROS) are implicated in induction of inflammatory response and cartilage degradation in osteoarthritis (OA). Melatonin has been shown to improve the chondrogenic differentiation and promote cartilage matrix synthesis in mesenchymal stem cells. However, the underlying mechanisms of melatonin-regulated antioxidant activity in OA cartilage are not known. The aim of this study was to explore the effect of melatonin on nuclear factor-erythroid 2-related factor 2 (NRF2), a key antioxidant tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…[ 37 ] Enhancement of Nrf2 signaling may improve catalase and superoxide dismutase expression and prevent ROS overproduction. [ 38 ] However, Nrf2 deficiency exacerbates the neuronal death associated with the disease, increasing neuroinflammation and protein aggregation. [ 39 ] In this study, we found that overexpression of Nrf2 and Tempol synergistically alleviates LPS‐induced oxidative stress in BEAS‐2B cells and inhibits cell ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…[ 37 ] Enhancement of Nrf2 signaling may improve catalase and superoxide dismutase expression and prevent ROS overproduction. [ 38 ] However, Nrf2 deficiency exacerbates the neuronal death associated with the disease, increasing neuroinflammation and protein aggregation. [ 39 ] In this study, we found that overexpression of Nrf2 and Tempol synergistically alleviates LPS‐induced oxidative stress in BEAS‐2B cells and inhibits cell ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies systematically reported the pivotal role of the melatonin‐SIRT1 axis in controlling the fate of chondrocytes and antagonizing OA. [ 63 ] Melatonin has a hepatoprotective effect on mitochondrial‐derived free radicals‐stimulated autophagic cell death, which is dependent on SIRT3/SOD2 pathway activation. [ 64 ] Furthermore, the Warburg effect during lung cancer development could be reversed by melatonin‐SIRT3‐stimulated mitochondrial membrane polarization and the activities of complex I and IV in ETC.…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin acts as an effective antioxidant, regulating the homeostasis of the cartilage matrix through the Nrf2 signaling pathway. This is evidenced by the increased expression of Nrf2 in melatonin-treated chondrocytes, which led to a reduction of intracellular ROS levels and a significant elevation in the expression of SOD1, SOD2, CAT, and HO-1 ( 136 ). The expression of Nrf2 and antioxidant enzymes could be significantly inhibited by miR-146a, which was markedly elevated in OA chondrocyte.…”
Section: Melatonin Targeting Oxidative Stress Inflammation and Chondr...mentioning
confidence: 99%
“…The expression of Nrf2 and antioxidant enzymes could be significantly inhibited by miR-146a, which was markedly elevated in OA chondrocyte. Moreover, overexpression of miR-146a reduced the level of Nrf2, thereby diminishing the protective effects of melatonin in articular cartilage of rats ( 136 ).…”
Section: Melatonin Targeting Oxidative Stress Inflammation and Chondr...mentioning
confidence: 99%